2020
DOI: 10.1101/2020.07.21.213405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-site co-mutations and 5’UTR CpG immunity escape drive the evolution of SARS-CoV-2

Abstract: The SARS-CoV-2 infected cases and the caused mortalities have been surging since the COVID-19 pandemic. Viral mutations emerge during the virus circulating in the population, which is shaping the viral infectivity and pathogenicity. Here we extensively analyzed 6698 SARS-CoV-2 whole genome sequences with specific sample collection dates in NCBI database. We found that four mutations, i.e., 5’UTR_c-241-t, NSP3_c-3037-t, NSP12_c-14408-t, and S_a-23403-g, became the dominant variants and each of them represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Our CpG net gain analysis showed a decline, indicating that the number of total CpG losses overrides their gain (Figure S4), in agreement with recently published observations (Wang et al 2020; Wei et al 2020; Zhang et al 2020). Similar to other coronavirus genomes, SARS-CoV-2 has a low CpG frequency around 1.5%, while the expected frequency is 3.6% (Wang et al 2020).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our CpG net gain analysis showed a decline, indicating that the number of total CpG losses overrides their gain (Figure S4), in agreement with recently published observations (Wang et al 2020; Wei et al 2020; Zhang et al 2020). Similar to other coronavirus genomes, SARS-CoV-2 has a low CpG frequency around 1.5%, while the expected frequency is 3.6% (Wang et al 2020).…”
Section: Resultssupporting
confidence: 92%
“…The remaining dinucleotides showed relative stability across the time period. Interestingly, recent reports showed the reduction of CpG dinucleotides in 5’-UTR and ORF1ab regions (Wang et al 2020; Wei et al 2020; Zhang et al 2020). When analyzing the context of genomic sites undergoing C>U changes we noticed an enrichment for 5’-UCG-3’ motifs (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple genetic viral mutations may also co-exist and co-evolve with the host population ( 31 ). Our recent study of 6698 SARS-CoV-2 whole-genome sequences revealed four dominant mutations, including 5’UTR_c-241-t, NSP3_c-3037-t, NSP12_c-14408-t, and S_a-23403-g ( 33 ). These mutational changes in viral genomes all contribute to the rapid viral evolution and enhance viral transmission and long-term survival rates.…”
Section: Illustration Of the Hpi Postulates With Host-coronavirus Int...mentioning
confidence: 99%